Risk stratification in patients with nonischemic cardiomyopathy and ventricular arrhythmias based on quantification of intramural delayed enhancement on cardiac magnetic resonance imaging. (18th May 2020) - Ghannam, Michael; Siontis, Konstantinos C.; Cochet, Hubert; Jais, Pierre; Juhoor, Mehdi; Attili, Anil; Sharaf‐Dabbagh, Ghaith; Latchamsetty, Rakesh; Jongnarangsin, Krit; Morady, Fred; Bogun, Frank
Abstract: Introduction: Intramural scarring is a risk factor for sudden cardiac death. The objective of this study was to determine the value of scar quantification for risk stratification in patients with nonischemic cardiomyopathy (NICM) undergoing ablation procedures for ventricular arrhythmias (VA). Methods and Results: Cardiac late gadolinium‐enhanced magnetic resonance imaging was performed in patients with NICM referred for ablation of premature ventricular complexes or ventricular tachycardia (VT). Only patients with intramural delayed enhancement were included. Scar volume was measured and correlated with immediate and long‐term outcomes. Receiver operator curves, Wilcoxon signed‐rank testing, and logistic regression were used to compare patient characteristics. The study consisted of 99 patients (74 males, mean age: 59.6 [54.0‐68.1] years, ejection fraction [EF]: 46.0 [35.0‐60.0]%). Patients without clinical VT or inducible VT had smaller total and core scar size compared to patients with a history of VT or inducible VT (total scar 1.12 [0.74‐1.79] cm 3 vs 7.45 [4.16‐12.21] cm 3, P < .001). A total scar volume of greater than or equal to 2.78 cm 3 was associated with inducibility of VT (AUC 0.94, 95% CI [0.89‐0.98], sensitivity 85%, specificity 90%). Scar volume was associated with VT inducibility independent of a prior history of VT or the preprocedure EF (adjusted OR 1.67 [1.24‐2.24]/cm 3, P < .01). Conclusion: Quantification of scar size in patients with intramural scarring is useful for risk stratification in patients with NICM and VA independent of the EF or a prior history of VT. Scar characteristics of patients without a history of VT who have inducible VT are similar to patients with a history of VT.